Transcriptional Regulation of Carbohydrate Utilization Pathways in the Bifidobacterium Genus - Khoroshkin, Matvei S.; Leyn, Semen A.; Van Sinderen, Douwe; Rodionov, Dmitry A. (Frontiers in Microbiology, 2016)
Bifidobacteria, which represent common commensals of mammalian gut, are believed to have positive effects on human health. The influence of certain non-digestible carbohydrates (and their use as so-called prebiotics) on growth and metabolic activity of bifidobacteria is of increasing interest; however, mechanisms of transcriptional control of carbohydrate metabolism are poorly understood in these species. We used a comparative genomics approach to reconstruct carbohydrate utilization pathways and transcriptional regulons in 10 Bifidobacterium genomes. Analysis of regulatory gene regions revealed candidate DNA motifs and reconstructed regulons for 268 transcription factors from the LacI, ROK, DeoR, AraC, GntR, and TetR families that form 64 orthologous groups of regulators. Most of the reconstructed regulons are local and control specific catabolic pathways for host- and diet-derived glycans and monosaccharides. Mosaic distributions of many of these local regulators across Bifidobacterium species correlate with distribution of corresponding catabolic pathways. In contrast, the maltose, galactose, sucrose, and fructose regulons, as well as a novel global LacI-family regulator that is predicted to control the central carbohydrate metabolism and arabinose catabolism genes, are universally present in all 10 studied bifidobacteria. A novel group of TetR-family regulators presumably controls the glucoside and galactoside utilization pathways. Paralogs of the ribose repressor RbsR control the pyrimidine nucleoside utilization genes. Multiple paralogs of the maltose regulator MalR co-regulate large sets of genes involved in maltodextrin utilization. The inferred metabolic regulons provide new insights on diverse carbohydrate utilization networks in bifidobacteria that can be employed in metabolic modeling, phenotype prediction and the rational development of novel prebiotics.